Comparison of 3 Rates for the Continuous Infusion of Mivacurium During Ambulatory Vitreoretinal Surgery Under General Anesthesia: A Prospective, Randomized, Controlled Clinical Trial - Zhang Y; Xi C; Yue J; Zhao M; Wang G (Dove Medical Press, 2022)
Yi Zhang,1,* Chunhua Xi,1,* Jianying Yue,1 Mengmeng Zhao,2 Guyan Wang1 1Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of China; 2Operation Center, Beijing Tongren Hospital, Capital Medical University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Guyan Wang, Department of Anesthesiology, Beijing Tongren Hospital, Capital Medical University, 1 Dongjiaominxiang Road, Dongcheng District, Beijing, 100730, People's Republic of China, Tel +86-10-58268101, Email guyanwang2006@163.comPurpose: Mivacurium, the shortest-acting benzylisoquinoline nondepolarizing neuromuscular blocker used in clinical practice, is suitable for short-term ambulatory operations under general anesthesia. We investigated the neuromuscular blockade effect of different maintenance doses of mivacurium during ambulatory vitreoretinal surgery under general anesthesia and tried to determine the appropriate maintenance dose.Patients and Methods: Ninety-nine patients undergoing general anesthesia for elective ambulatory vitreoretinal surgery were randomly divided into three groups using the random number table method. Patients received three maintenance doses of mivacurium during surgery as follows: 3 μg/(kg·min) in group M1 (n = 33), 6 μg/(kg·min) in group M2 (n = 33), and 9 μg/(kg·min) in group M3 (n = 33). The primary outcome was the time from mivacurium withdrawal to a train-of-four stimulation ratio (TOFr) ≥ 0.9, and the secondary outcomes were the time from mivacurium withdrawal to TOFr ≥ 0.7, extubation time, incidence of TOFr < 0.9 after surgery and neuromuscular block effect.Results: The time from mivacurium withdrawal to TOFr ≥ 0.9 and to TOFr ≥ 0.7 was significantly longer in group M3 than in groups M1 and M2 (25.6± 7.2 min vs 16.4± 5.9 min and 18.6± 5.3 min, P < 0.001; 22.1± 6.3 min vs 13.6 ± 5.8 min and 15.5 ± 4.8 min; P < 0.001, respectively). There was a significant difference in the extubation time, the incidence of TOFr < 0.9 during extubation and upon leaving the operating room between group M3 and group M1 (all P < 0.05), but there was no such significant difference between group M2 and group M1 (all P > 0.05). The intraoperative depth of neuromuscular blockade in the three groups was significantly different, with 69.7% shallow block in group M1, 75.8% moderate block in group M2 and 63.6% deep block in group M3 (P < 0.001). One patient in group M1 experienced slight body movement during the operation.Conclusion: An intraoperative continuous infusion of 6 μg/(kg·min) mivacurium can not only achieve good postoperative recovery but also provide a satisfactory neuromuscular blockade effect during surgery, and this maintenance dose is suitable for neuromuscular blockade during ambulatory vitreoretinal surgery.Keywords: mivacurium, vitreoretinal surgery, neuromuscular blocking agents, neuromuscular monitoring, postoperative period